KLASIFIKASI INVENTORI DENGAN ABC/XYZ ANALYSIS DAN MENGOPTIMALKAN SAFETY STOCK DI PT. X - Erwin Pratama Wijaya; I Gede Agus Widyadana (Jurnal Titra, 2015)
PT. X is one of the leading companies in the cigarette industry in Indonesia. The company aims to do continuous improvement of their finished goods distribution with the requested schedules and quantities. The company also wants to have DIM ready as scheduled with the required quantities based on the production needs. The first measure that can be taken is the creation of safety stock for the two varieties of the inventory as a mean to act as a cushion whenever a stockout occurs that can be caused by distribution delay by PT.X as well as vendor. The determining factor for the safety stock is the classification of every inventory. The classification of ABC/XYZ is needed before determining the safety stock. This will help the company to determine the inventory, predictable or forecasted or not, based on the volatility of the inventory itself. The classification is also used to help the company to see which inventory that should be prioritized for the storing process.